Russian-Chinese Relations: some Vectors and Development Prospects - O. E. Grishin; O. S. Pronina (Проблемы постсоветского пространства, 2017)
The article analyzes the Russian-Chinese relations at the present stage of their development. Considered grounds for mutually beneficial relations between China and Russia. These vectors of their formation in the short term, as well as some marked differences. Some results on the important areas of Russian-Chinese cooperation. The recommendations for its strengthening.